A Review of Teaching Sentence-Level Writing Skills to Students With Writing Difficulties and Learning Disabilities. (May 2013) - Datchuk, Shawn M.; Kubina, Richard M.
Students with writing difficulties and learning disabilities struggle with many aspects of the writing process, including use of sentence-level skills. This literature review summarizes results from 19 published articles that used single-case or group-experimental and quasi-experimental designs to investigate effects of intervention on the sentence-level skills of handwriting, sentence construction, and grammar/usage. Results suggest struggling writers benefited from intervention, particularly in handwriting and sentence construction, and transferred acquired skills to more complex tasks such as sentence writing and extended composition. Also presented are the implications for research and practice.